TWO BUY AND SELL IN ONE BUY AND SELL : HADITH PERSPECTIVE - Ade Supriatna; Wandy Zulkarnaen; Suparjiman Suparjiman (Universitas Dharma Wacana, 2022)
This article discusses the Hadith narrated by Hannad bin As Sariy bin Mush’ab about Two Buy and Sell in One Buy and Sell in Ṣunan al-Tirmidzi. This article was written using the Takhrīj al-Ḥadīts method. The data source is in the form of a narration of the Hadith in Ṣunan al-Tirmidzi about Two Buy and Sell in One Buy and Sell. The type of data is in the form of hadith text in Ṣunan al-Tirmidzi about Two Buy and Sell in One Buy and Sell complete sanad and matn. The data collection technique is done by tracing the Hadith narration about Two Buy and Sell in One Buy and Sell in Ṣunan al-Tirmidzi. The data analysis technique was carried out by applying the Sharḥ al-Ḥadīth method, both in the sanad and matn aspects. This article reveals that the hadith narrated by Hannad bin As Sariy bin Mush’ab about Two Buy and Sell in One Buy and Sell in Ṣunan al-Tirmidzi relates to the concept of Hybrid Contract in Sharia Bank.